Vitamin D intoxication caused by ingestion of commercial cat food in three kittens. Issue 8 (August 2013) - Wehner, Astrid; Katzenberger, Julia; Groth, Anna; Dorsch, Roswitha; Koelle, Petra; Hartmann, Katrin; Weber, Karin
Two siblings, a 6-month-old sexually intact male weighing 2.5 kg (cat 1) and a sexually intact female (cat 2) British Shorthair cat weighing 2.3 kg, were examined because of a 3-week history of polyuria, lethargy and laboured breathing. One year previously, another sibling (cat 3) had been presented because of similar, yet more severe, clinical signs at the age of 5 months. Physical examination revealed lethargy, dehydration and polypnoea with slightly increased inspiratory effort. Diagnostic investigation revealed severe hypercalcaemia (cats 1–3), renal azotaemia (cats 1 and 3) and a radiologically generalised miliary interstitial pattern of the lungs (cats 1–3) attributable to hypervitaminosis D caused by ingestion of commercial cat food. Cat 3 was euthanased. Cats 1 and 2 were treated with isotonic saline solution (180 ml/kg IV daily), sucralfate (30 mg/kg PO q12h), terbutaline (only cat 1: 0.1 mg/kg SC q4h), furosemide (1.5 mg/kg IV q8h) and tapering doses of prednisolone. Cat 2 was normal on day 14. Cat 1 had stable renal disease and was followed up to day 672. The radiological generalised military interstitial pattern of the lungs had improved markedly. Excessive cholecalciferol-containing commercially available cat food poses a great hazard to cats. Supportive treatment may result in long-term survival and improvement of radiological pulmonary abnormalities.